1993
DOI: 10.1002/ana.410340210
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion molecule expression on cerebrospinal fluid T lymphocytes: Evidence for common recruitment mechanisms in multiple sclerosis, aseptic meningitis, and normal controls

Abstract: The expression of T-cell surface antigens was investigated in the cerebrospinal fluid (CSF) and peripheral blood of 11 patients with multiple sclerosis, 6 patients with aseptic meningitis, and 16 healthy subjects. A panel of monoclonal antibodies to adhesion and activation proteins was used in combination with an anti-CD3 antibody in dual-color flow cytometry. The problem of low cell numbers in the CSF from normal individuals was overcome by use of a modified staining procedure in microtiter plates, enabling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
47
3
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(62 citation statements)
references
References 43 publications
9
47
3
3
Order By: Relevance
“…Contrary to our finding is a report describing a lower prevalence of VLA-4-bearing lymphocytes in the blood of MS patients compared with normal control subjects [29]. However, this earlier study only monitored lymphocytes with a high expression of VLA-4 obtained from patients with benign relapsing-remitting MS (EDSS range 0-2 .…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to our finding is a report describing a lower prevalence of VLA-4-bearing lymphocytes in the blood of MS patients compared with normal control subjects [29]. However, this earlier study only monitored lymphocytes with a high expression of VLA-4 obtained from patients with benign relapsing-remitting MS (EDSS range 0-2 .…”
Section: Discussioncontrasting
confidence: 99%
“…ICAM-1 is expressed on resting endothelium in various tissues including parenchymal vessels in noninflamed human brain (18,31). ICAM-1 mediates firm arrest of circulating T cells through binding of lymphocyte function-associated antigen 1 (integrin ␣ L ␤ 2 ), which is expressed by a majority of CSF T cells from both healthy volunteers and patients with CNS inflammation, and on virtually all CNS-infiltrating leukocytes in inflammatory multiple sclerosis lesions (18,32,33). ICAM-1 was constitutively expressed in the choroid plexus of healthy mice and mediated binding of lymphocytes in vitro with a StamperWoodroof assay (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Because CSF of healthy controls is usually not available due to ethical considerations (36), patients with noninflammatory neurological disorders (NIND controls) are often included instead (37). However, Svenningsson et al (38,39) did study normal CSF by assessing the percentages of lymphocyte subsets in CSF of 34 healthy individuals, after informed consent, with 2-or 3-color flow cytometry. In addition, we studied both absolute numbers and percentages of leukocyte, lymphocyte, T lymphocyte, and dendritic cell subsets by six-color flow cytometry in 84 individuals without neurological disease undergoing spinal anesthesia (Table 1; 40).…”
Section: Cellular Composition Of Normal Csfmentioning
confidence: 99%
“…In addition, we studied both absolute numbers and percentages of leukocyte, lymphocyte, T lymphocyte, and dendritic cell subsets by six-color flow cytometry in 84 individuals without neurological disease undergoing spinal anesthesia (Table 1; 40). The two published studies (38,39), as well as our data (40), showed that normal CSF is predominantly composed of CD4 þ T lymphocytes, mostly with a central memory phenotype, and in addition contains very low frequencies of B lymphocytes, NK cells, and NKT lymphocytes (Table 1). Dendritic cells, both myeloid as well as plasmacytoid, were also present in normal CSF, although in very low frequencies (Table 1;40,41).…”
Section: Cellular Composition Of Normal Csfmentioning
confidence: 99%